Extradigit Glomus Tumor Causing Abdominal Pain -A Case Report- - Kim, Yeon Dong (The Korean Pain Society, 2012)
Glomus tumors are small vascular tumors that are usually benign and rarely occur. They originate from glomus bodies and present in the reticular dermis. They are clinically distinguished by their small size and their ability to cause extreme pain. Most of these tumors are subungually located. However, atypical locations of the tumors sometimes cause misdiagnosis, particularly when the lesion is rarely reported. Therefore, we report a case of glomus tumor which presented with chronic abdominal pain, found in the abdominal wall that has never been reported before.